PELATIHAN PENINGKATAN KUALITAS LAYANAN DAN KOMUNIKASI BAGI MANAJEMEN OPERASIONAL PENGELOLA DAYA TARIK WISATA JATILUWIH, TABANAN - Wayan Agung Panca P; Putu Herny Susanti; I Nengah Sudipa; I Gusti Agung Ayu Widiastri (JURNAL SEWAKA BHAKTI, 2026)
Jatiluwih Tourism Village, a UNESCO World Cultural Heritage site in Bali, faces challenges in maintaining service quality, effective communication, and operational management amid increasing tourist arrivals. This community service program aimed to enhance the capacity of management and operational staff in delivering high-quality services, improving communicative English skills, strengthening storytelling competencies, and promoting service excellence based on Balinese cultural values and local wisdom. The program employed a participatory and collaborative approach involving needs assessment, training design, implementation through interactive workshops and role-playing activities, and evaluation. Training materials covered tourism storytelling, communicative English for hospitality, service ethics, and culturally based human resource management. Evaluation results indicated that all training aspects were rated in the “very good” category, with scores ranging from 81.1% to 90.0%. Participants demonstrated improved storytelling abilities, greater confidence in using English for tourism services, and enhanced understanding of hospitality principles rooted in local values such as Tri Hita Karana, Tat Twam Asi, and the TULUS & NAU service concept. The program contributed positively to strengthening human resource competencies and supporting sustainable tourism development in Jatiluwih Tourism Village through culturally grounded and visitor-oriented service practices.